Peningkatan Kapasitas Dosen Pembimbing Praktik Kerja Lapangan melalui Bimbingan Teknis dan Lokakarya Partisipatif di Institut Teknologi Mitra Gama - Dori Gusti Alex Candra; Atika Fauziyyah; Khelvin Ovela Putra; Zaharani Yusno; Sonya Ostha Laurency; Eka Sofiati; M. Agung Vafky Ideal; Tomy Nanda Putra; Hafizh Gusra (Universitas Dirgantara Marsekal Suryadarma, 2026)
Field Work Practice (PKL) serves to bridge the gap between the competencies taught in higher education and the actual needs of the business and industrial sectors (DU/DI). However, the effectiveness of PKL is often hindered by a focus on administrative guidance alone. This Community Service (PkM) activity aims to enhance the capacity of Field Supervisors (DPL) at the Mitra Gama Institute of Technology (ITMG) as the internal target audience. The activity was held on May 1–3, 2025, in the ITMG Auditorium for a duration of 24 instructional hours, involving 30 active faculty members at Mitra Gama Institute of Technology who were selected based on specific inclusion criteria. The implementation methods included technical guidance, focus group discussions (FGDs), and workshops. The activity was evaluated using a one-group pretest-posttest pre-experimental design through structured questionnaires, as well as an analysis of the feasibility of the Follow-Up Action Plan (RTL) documents. Data were analyzed using descriptive statistics and content analysis. The results of the program showed an increase in participants’ cognitive knowledge and managerial readiness, as evidenced by a 38% increase in the average post-test score compared to the pre-test score. In addition, the program successfully facilitated the preparation of 30 independent Action Plan (RTL) documents and produced an institutional output in the form of a draft proposal for restructuring the internship evaluation rubric with a 50:50 ratio.